On the first record of Calanthe lamellosa (Orchidaceae) from India with notes on typification - Moaakum; Dey , S.; Bhattacharjee, A.; Neikha, T. (Rheedea, 2022)
Calanthe lamellosa Rolfe (Orchidaceae) is reported here for the first time from India and a detailed description, photographs and drawing are provided. Its affinity with Calanthe brevicornu Lindl. is discussed and a lectotype is designated for C. lamellosa from the available original material (syntypes). Further, a lectotype is designated for Calanthe yunnanensis Rolfe, a heterotypic synonym of C. lamellosa.